Relationships among player load, high-hntensity intermittent running ability, and injury risk in professional rugby league players - Hulin, B. T.; Gabbett, T. J; Pickworth, N. J.; Johnston, R. D.; Jenkins, D. G. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine relationships among physical performance, workload, and injury risk in professional rugby league players. Methods: Maximal-effort (n=112) and submaximal (n=1084) running performances of 45 players were recorded from 1 club over 2 consecutive seasons. Poorer and better submaximal running performance was determined by higher and lower exercise heart rates, respectively. Exponentially weighted moving averages and daily rolling averages were used to assess microtechnology-derived acute and chronic field-based workloads. The associations among within-individual submaximal running performance, workload, and noncontact lower-limb injury were then investigated. Results: The injury risk associated with poorer submaximal performance was "likely" greater than stable (relative risk=1.8; 90% confidence interval, 0.9-3.7) and better submaximal performance (relative risk=2.0; 90% confidence interval, 0.9-4.4). Compared with greater submaximal performance, poorer performance was associated with lower chronic workloads (effect size [d]=0.82 [0.13], large) and higher acute:chronic workload ratios (d=0.49 [0.14], small). Chronic workload demonstrated a "nearly perfect" positive relationship with maximal-effort running performance (exponentially weighted moving average, R2=.91 [.15]; rolling average, R2=.91 [.14]). At acute:chronic workload ratios >1.9, no differences in injury risk were found between rolling average and exponentially weighted moving average methods (relative risk=1.1; 90% confidence interval, 0.3-3.8; unclear). Conclusions: Reductions in submaximal running performance are related with low chronic workloads, high acute:chronic workload ratios, and increased injury risk. These findings demonstrate that a submaximal running assessment can be used to provide information on physical performance and injury risk in professional rugby league players.